PHARMACOGNOSTIC STUDY AND DEVELOMENT OF QUALITY PARAMETERS OF WHOLE PLANTS OF TRICHODESMA INDICUM (Linn.) R.Br. - CHIDAMBARAM, AZHAGU RAMAN; ARUNA, AJITHADAS (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Trichodesma indicum is a common weed widely present in India. No detailed work on its pharmacognostical and development of quality parameters has been done on Trichodesma indicum. The present study deals with macroscopical, cytomorphologial and quantitative microscopy of the leaf and macroscopical and cytomorphological evaluation of the stem and root. Establishment of its quality parameters include physicochemical and phytochmical evaluation of the powder as well as the extract. Macroscopical and microscopical evaluation of leaf, stem and root gave special identification characters. Several physicochemical parameters were also performed. Phytochemical investigation reveals the presence of tannins, flavonoids, phytosterols, sugars, saponins, protein and free amino acids. This is important tool for the standardization of plant materials, isolation of bioactive principles, screening of pharmacological activities, ensuring the quality of formulation and also useful to distinguish it from its related species. Key words: Microscopical study, physicochemical study, Phytochemical study, Trichodesma indicum (Linn) R.Br